Accuracy of Intraoperative Frozen Section of Sentinel Lymph Nodes After Neoadjuvant Chemotherapy for Breast Carcinoma. (October 2019) - Grabenstetter, Anne; Moo, Tracy-Ann; Hajiyeva, Sabina; Schüffler, Peter J.; Khattar, Pallavi; Friedlander, Maria A.; McCormack, Maura A.; Raiss, Monica; Zabor, Emily C.; Barrio, Andrea; Morrow, Monica; Edelweiss, Marcia
Abstract : False-negative (FN) intraoperative frozen section (FS) results of sentinel lymph nodes (SLN) have been reported to be more common after neoadjuvant chemotherapy (NAC) in the primary surgical setting. We evaluated SLN FS assessment in breast cancer patients treated with NAC to determine the FN rate and the histomorphologic factors associated with FN results. Patients who had FS SLN assessment following NAC from July 2008 to July 2017 were identified. Of the 711 SLN FS cases, 522 were negative, 181 positive, and 8 deferred. The FN rate was 5.4% (28/522). There were no false-positive results. Of the 8 deferred cases, 5 were positive on permanent section and 3 were negative. There was a higher frequency of micrometastasis and isolated tumor cells in FN cases ( P <0.001). There was a significant increase in tissue surface area present on permanent section slides compared with FS slides ( P <0.001), highlighting the inherent technical limitations of FS and histologic under-sampling of tissue which leads to most FN results. The majority (25/28, 89%) of FN cases had metastatic foci identified exclusively on permanent sections and were not due to a true diagnostic interpretation error. FN cases were more frequently estrogen receptor positive ( P <0.001), progesterone receptor positive ( P =0.001), human epidermal growth factor receptor-2 negative ( P =0.009) and histologic grade 1 ( P =0.015), which most likely reflects the lower rates of pathologic complete response in these tumors. Despite its limitations, FS is a reliable modality to assess the presence of SLN metastases in NAC treated patients.